Extensive Aplasia Cutis Congenita Encircling the Trunk Associated with Fetus Papyraceus - Alexander K. C. Leung; Kin Fon Leong; Joseph M. Lam (Hindawi Limited, 2020)
Aplasia cutis congenita associated with fetus papyraceus, though rare, is well known. On the other hand, aplasia cutis congenita associated with fetus papyraceus presenting with symmetrical circumferential scarring encircling the trunk has not been previously reported. Herein, we report a 2-month-old girl with symmetrical circumferential scarring encircling the trunk associated with fetus papyraceus.